1982
DOI: 10.1007/bf00334146
|View full text |Cite
|
Sign up to set email alerts
|

Lysis of Escherichia coli by induction of cloned ϕX174 genes

Abstract: The largest of the fragments produced by AluI digestion of phi X174 RFI DNA comprises genes E and J as well as parts of genes D and F. This DNA fragment (1007 bp) was cloned into the lac z' gene of plasmid pUR222. In the recombinant plasmid pUH12, transcription of the phi X174 genes is controlled by the lac p-o region. Induction of the cloned genes by addition of the lac inducer, IPTG, resulted in lysis of the bacteria. Cloning of the corresponding AluI-fragment from phi X174am3 DNA, carrying an amber mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
88
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 18 publications
1
88
0
Order By: Relevance
“…The same injury then would allow the release of autolytic enzymes to the cell wall and initiate lysis of the bacteria. This model is formally analogous to models proposed for the mechanism of lysis by bacteriophages in which the release of phage progeny is preceded by membrane injury through the insertion of a holin protein into the bacterial membrane (32,33). Our model also is analogous to the proposed mode of action of nisin at the level of lipid II (34).…”
Section: Discussionmentioning
confidence: 52%
“…The same injury then would allow the release of autolytic enzymes to the cell wall and initiate lysis of the bacteria. This model is formally analogous to models proposed for the mechanism of lysis by bacteriophages in which the release of phage progeny is preceded by membrane injury through the insertion of a holin protein into the bacterial membrane (32,33). Our model also is analogous to the proposed mode of action of nisin at the level of lipid II (34).…”
Section: Discussionmentioning
confidence: 52%
“…2,3 Later the temperature-sensitive λ-system (λp L /λp R -cI857) has proven to be more suitable for quick and efficient lysis without the need of any addition of chemical inducers. 18 Since the λ repressor cI857 shows incipient expression of downstream gene E at temperatures above 30°C the temperature sensitivity of the system was optimized to meet more favorable fermentation temperatures of 35°C or higher.…”
Section: Bg-production Processmentioning
confidence: 99%
“…1 More than 16 years later, when genetic engineering had been developed, it could be shown that its sole expression after cloning is sufficient to cause subsequent lysis of E. coli. 2,3 E was the first lethal gene for bacteria which could be silenced on plasmids. When established in non-host range bacteria of the phage expression of E converts Gram-negative bacteria into BGs whereas Gram-positive bacteria are killed without lysis.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] In this concept study the ice nucleation protein Z (InaZ) of Pseudomonas syringae was expressed in E. coli which were further processed to Bacterial Ghosts (BGs). BGs are empty cell envelopes of Gram-negative bacteria produced by the expression of cloned gene E of bacteriophage Phix174 [31][32][33][34][35] The conversion of a single living bacterium into a BG is a rapid process in the range of milliseconds 35 and can be characterized by puncturing the bacterium cell envelope from the inside to the outside expelling its cytoplasmic content to the surrounding medium. Electron micrographs of this process can be depicted from the original description in 1990 33 and a more recent one using this Emediated lysis of E. coli for cryo-electron tomography of membrane protein complexes within the native cell envelope complex remaining intact after E-mediated lysis.…”
Section: Introductionmentioning
confidence: 99%